2012
DOI: 10.4028/www.scientific.net/amr.554-556.1475
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Fatigue Effect of Black Soybean Peptide in Mice

Abstract: The anti-fatigue activity evaluation was carried out with black soybean peptide in mice. The results show that, the middle and high dose active peptides can significantly (P<0.01) prolong swimming time, blood lactic acid can be reduced notable (P<0.01), and improving the liver glycogen storage status greatly (P<0.01) by infusing with black soybean peptide. The results suggest that black soybean peptide has obvious anti-fatigue effect, and the anti-fatigue action will improve by increasing dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Approximately one third of soybean isoflavones remain in okara. Thus, this by-product, in addition to having the potential to be used as a source of nutrients, it is also a source of isoflavones (LI et al, 2012). Studies indicate that the consumption of soybean by-products and their derivatives provides health benefits, such as prevention and therapeutic treatment of cardiovascular diseases reduced risk of cancer and osteoporosis, and alleviation of menopausal symptoms (MOLINA; FEIHRMANN, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately one third of soybean isoflavones remain in okara. Thus, this by-product, in addition to having the potential to be used as a source of nutrients, it is also a source of isoflavones (LI et al, 2012). Studies indicate that the consumption of soybean by-products and their derivatives provides health benefits, such as prevention and therapeutic treatment of cardiovascular diseases reduced risk of cancer and osteoporosis, and alleviation of menopausal symptoms (MOLINA; FEIHRMANN, 2009).…”
mentioning
confidence: 99%
“…Data from EI, SV, L*, and chrome a* and b* of the snacks were evaluated by analysis of variance with the construction of multiple regression models and level curves to identify the effect of the independent variables on the responses using the Statistica software (Statsoft,Statistica 7.0,Tulsa,USA). Based on the significant mathematical models (P <0.10) and using the function Response Desirability Profiling of the software Statistica, the most desirable snack depending on the moisture and extrusion temperature used (LI et al, 2012;LIMBERGER et al, 2009). In the present study, the best extrusion condition was determined considering the aspects of expansion and color as a function of the mixture moisture and temperature in the third zone of the extruder, in addition to the physical and chemical quality parameters of the snacks produced using the best technological condition.…”
mentioning
confidence: 99%
“…This decrease may be related to fatigue, so if the seven amino acids are present in the diet at a high concentration, exercise capacity might be increased and fatigue might be reduced. Additionally, lysine, histidine, methionine, cysteine and phenylalanine have showed antioxidant activity or to be closely concerned with promoting the generation of antioxidant activity [ 20 ]. Accordingly, the presence of high concentrations of such amino acids would lead to free radicals removing and consequently, prevention of their generation would reduce fatigue.…”
Section: Resultsmentioning
confidence: 99%
“…Glu is the more abundant amino acid in SMOT (12.28%) and is also rich in Asp (7.04%) and Arg (9.40%). Li et al (2012) found that black soybean peptides contained 11.02% Glu and 6.83% Asp respectively, suggesting that they may have potential anti-fatigue effects. Glu has been found to have a very positive effect on the nervous system and to be helpful during exercise (You et al, 2011) ; Asp is thought to lower blood ammonia concentrations (Xu et al, 2015) , thereby delaying the onset of fatigue.…”
Section: Molecular Weight Distribution and Amino Acid Composition Of Smotmentioning
confidence: 96%